2015
DOI: 10.3109/09546634.2015.1054779
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma originating from cutaneous cysts: The Henry Ford Experience and review of the literature

Abstract: Given the extremely low incidence, propensity of malignant lesions to become symptomatic and efficacy of treatment, we do not recommend routine excision of all epidermal cysts. Instead, we recommend excision and pathology for all symptomatic epidermal cysts, or those that rapidly grow, or do not respond to medical therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 17 publications
0
28
1
2
Order By: Relevance
“…The incidence of SCC developing from an epidermal inclusion cyst has been estimated to range from 0.011 to 0.045% [ 1 ]. After a review of the literature, we found 41 well-documented cases of SCC arising from cutaneous epidermal inclusion cysts [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Our findings are summarized in Table 1 and Table 2 , which shows an increase in the number of reported cases of SCC arising from epidermal inclusion cysts since 2010.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of SCC developing from an epidermal inclusion cyst has been estimated to range from 0.011 to 0.045% [ 1 ]. After a review of the literature, we found 41 well-documented cases of SCC arising from cutaneous epidermal inclusion cysts [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Our findings are summarized in Table 1 and Table 2 , which shows an increase in the number of reported cases of SCC arising from epidermal inclusion cysts since 2010.…”
Section: Discussionmentioning
confidence: 99%
“…The keratin produced by these cysts is similar to keratin derived from human hair isthmus (Kaya & Saurat, 2018). The combination of trichilemmal cysts and SCC is a very rare occasion (Veenstra, Choudhry, Krajenta, & Eide, 2016). Table 1.…”
mentioning
confidence: 95%
“…During 6 months of follow-up, no relapse of the lesions was observed.Cutaneous collision tumors with SCC are uncommon. Reports described combinations of SCC with epidermal cysts(Veenstra, Choudhry, Krajenta, & Eide, 2016), melanoma(Scruggs, Rensvold, Parekh, & Butler, 2011), and apocrine carcinoma(Lorusso, Sarma, Fazekas-May, Roth, & Sarwar, 2004). A collision of SCC with trichilemmal cysts is exceptionally rare.…”
mentioning
confidence: 99%
“…The lesion was excised with 0.1 mm margins and the patient underwent radiotherapy after the operation. SCCs arising within pre‐existing cysts are extremely rare and have an unknown transformation mechanism . Chronic inflammation, immunosuppression and trauma are recognised risk factors .…”
mentioning
confidence: 99%
“…SCCs arising within pre‐existing cysts are extremely rare and have an unknown transformation mechanism . Chronic inflammation, immunosuppression and trauma are recognised risk factors . A history of rapid growth and a failure to medically treat a suspected infected cyst should raise suspicion for malignancy …”
mentioning
confidence: 99%